Replication Data for: Variable responses of carbon and nitrogen contents in vegetation and soil to herbivory and warming in high-Arctic tundra - Petit Bon, Matteo; Böhner, Hanna; Bråthen, Kari Anne; Ravolainen, Virve Tuulia; Jónsdóttir, Ingibjörg Svala (DataverseNO, 2017)
Dataset used to ask to what extent major ecosystem compartments (vascular plants, mosses, and soil) differ in their short-term chemical responsiveness (i.e. sensitivity and magnitute) to herbivory and warming in the high-Arctic tundra (Svalbard).